‘सावित्रीको बाख्रो’ कथामा वर्णविन्यास वक्रता - Dhakal, Dilliram (Haimaprabha, 2025)
Among the Eastern literary sciences, the Vakrokti is an important coordinating principle. In the Vakrokti principle, which is established as a coordination of the linguistic skills of the preceding flavor, the elegiac beauty of sound, the allegory and the manner, Kuntaka has analyzed six types, namely, the varnavinyas vakrata, the padapurvaadha vakrata, the padaparardha vakrata, the vakra vakrata, the vakra vakrata, the vakra vakrata, and the prabhava vakrata. Of these six types, the story has been studied and analyzed in the present article, considering the varnavinyas vakrata as the main basis. In the present article, which uses the purposive sampling method, the story content has been used as the main source. In the course of analyzing the story, the Vakrokti principle has been briefly discussed and among its six types, the varnavinyas vakrata and its sub-types, namely, one varnavinyas vakrata, two varnavinyas vakrata, multiple varnavinyas vakrata, vargantaryogisparsha varnavinyas vakrata, ta-la-nadi varnavinyas vakrata and rakaradi varnavinyas vakrata, have been considered as the main basis. The descriptive method has been used in the article using primary and secondary sources. In the present article, which uses the deductive method, conclusions have been drawn on the basis of the relativity of the alphabetic curvature.